Breastfeeding impact on patent ductus arteriosus closure in preterm newborns - A.O. Tovarnytska (Zaslavsky O.Yu., 2022)
Background. Patent ductus arteriosus (PDA) is a serious problem in clinical neonatology and pediatrics. Today treatment of PDA remains debatable because of high risk of complications with medical and invasive treatment. The purpose of the study was to determine the dependence of PDA closure on the type of feeding the newborn. Materials and methods. We have made a retrospective analysis of 300 case histories of children in neonatal units. We selected two comparison groups: the main group consisted of breastfed babies born at 37 weeks gestation (n = 102); controls - preterm infants who received artificial feeding since birth (n = 198). Results. At discharge from the hospital, 44 (14.7 ± 2.0 %) children had PDA (p < 0.05). The percentage of infants on artificial feeding with PDA was 2.3 times higher compared to breastfed babies: 18.2 ± 2.7 % versus 7.8 ± 2.7 % (p = 0.017 by χ2 test). Respiratory distress syndrome was more common in the control group as well: 72.7 ± 3.2 % versus 46.1 ± 4.9 % (p < 0.001). Additionally, the group of formula-fed children more often had severe complications of respiratory distress syndrome: respiratory failure type III - 25.8 ± 3.1 % versus12.7 ± 3.3 % (р = 0.009); development of bronchopulmonary dysplasia - 13.1 ± 2.4 % versus 2.9 ± 1.7 % (p = 0.005). The need for invasive mechanical ventilation in the intensive care unit was observed much less often in breastfed children. Moreover, the level of respiratory disorders (type II respiratory failure) in both groups differed insignificantly (p = 0.742): 24.5 ± 4.3 % in the main group and 26.3 ± 3.1 % in controls. Conclusions. Breastfeeding from the first days of life contributes to the closure of the ductus arteriosus and the favorable course of respiratory distress syndrome in premature babies.